2021
DOI: 10.1002/admi.202101155
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Hyaluronic Acid Semi‐Interpenetrated Hydrogel with Bull Spermatozoa: Studies of Sperm Attachment–Release and Sperm Quality

Abstract: The study of living systems in contact with biocompatible synthetic hydrogels is developing. The authors’ group is the first to propose use of polymeric materials to accomplish sperm selection process by attachment of bull sperm to hydrogel surfaces, this being a crucial step for successful assisted reproductive techniques (ARTs). Surfaces based on poly(N‐isopropylacrylamide) hydrogels (PNIPAM) and ionic and neutral copolymers are synthetized. Their physicochemical properties in aqueous and culture medium are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Sperm-OEC interactions may be modulated by glycosaminoglycans (GAG). There is evidence from in vitro studies that bull and human sperm bind to HA 14 , 15 , 32 . Although existing data are scarce and rather old, HA and HS have previously been reported as the two most abundant GAGs in the OF of post-pubertal cows, accounting for 39 and 26% of the total amounts of GAG, respectively 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sperm-OEC interactions may be modulated by glycosaminoglycans (GAG). There is evidence from in vitro studies that bull and human sperm bind to HA 14 , 15 , 32 . Although existing data are scarce and rather old, HA and HS have previously been reported as the two most abundant GAGs in the OF of post-pubertal cows, accounting for 39 and 26% of the total amounts of GAG, respectively 12 .…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that HA-binding proteins are present at the surface of bovine oviduct epithelial cells (OEC) 11 and on bull spermatozoa 13 . Motile bull spermatozoa have also been shown to be capable of binding to HA in vitro 14 , 15 . Therefore, HA is a good candidate for regulating sperm binding to the isthmic reservoir in cattle.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence from in vitro studies that bull and human sperm bind to HA 14,15,34 . Although existing data are scarce and rather old, HA and HS have previously been reported as the two most abundant GAGs in the OF of post-pubertal cows, accounting for 39 and 26% of the total amounts of GAG, respectively 12 .…”
Section: Sperm-oec Interactions May Be Modulated By Glycosaminoglycan...mentioning
confidence: 99%
“…Semi-interpenetration of hyaluronic acid in polyacrylamide hydrogels promotes cell adhesion of live spermatozoids while releasing dead ones. In that way, improvements in bovine sperm quality can be obtained [46]. Moreover, selection of bull sperm cells can be achieved [48].…”
Section: Cell Adhesion Surfacesmentioning
confidence: 99%